Kualitas Daging Domba Berdasarkan Keragaman, Jumlah Dan Cemaran Bakteri Di Pasar Tradisional Desa Klambir V Kecamatan Hamparan Perak Kabupaten Deli Serdang - Alfath Rusdhi; Tengku Gilang Pradana; Muhammad Sadiqulamin (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Meat is an essential food ingredient in meeting nutritional needs. The purpose of this research is to detect the total plate count and bacterial contamination in lamb meat. The research method used in this study is descriptive because it describes the characteristics of a population or a phenomenon that is being studied in a trial and error manner. From the observation data, 6 samples of lamb meat obtained from the traditional market in Kampung Lalang were analyzed using descriptive methods, which revealed the presence of Escherichia coli and Salmonella sp bacteria. The highest TPC analysis value was found in vendor 2 and vendor 3, sample 2, with a count of 6.55x106 cfu/g and 7.15x106 cfu/g, respectively, while the lowest contamination was found in vendor 1, sample 2, with a count of 4.57x105 cfu/g. These values are in accordance with the permissible limits of Escherichia coli (1 x 101 colonies/gram) and Salmonella sp (negative/25 grams) as set by the Indonesian National Standards (SNI). The results of the study indicate that 6 samples of lamb meat were not contaminated with Escherichia coli and Salmonella sp bacteria, demonstrating that the lamb meat sold in the traditional market of Klambir V Village complies with the Indonesian National Standards (SNI) and is suitable for consumption.